Red tides. - Edited by Tomotoshi Okaichi; Associate Editors, Yasuwo Fukuyo...[et al.]. (Tokyo Terra Scientific Pub. Co.; Dordrecht; Boston Kluwer Academic Publishers, 2004)
Includes bibliographical references.Series: Ocean sciences research; v.4
Keywords: Red tide; Red tide-- Environmental aspects